Efficient In Vivo Screening Method for the Identification of C4 Photosynthesis Inhibitors Based on Cell Suspensions of the Single-Cell C4 Plant Bienertia sinuspersici - Minges, Alexander; Janßen, Dominik; Offermann, Sascha; Groth, Georg (Frontiers in Plant Science, 2019)
The identification of novel herbicides is of crucial importance to modern agriculture. We developed an efficient in vivo assay based on oxygen evolution measurements using suspensions of chlorenchyma cells isolated from the single-cell C4 plant Bienertia sinuspersici to identify and characterize inhibitors of C4 photosynthesis. This novel approach fills the gap between conventional in vitro assays for inhibitors targeting C4 key enzymes and in vivo experiments on whole plants. The assay addresses inhibition of the target enzymes in a plant context thereby taking care of any reduced target inhibition due to metabolization or inadequate uptake of small molecule inhibitors across plant cell walls and membranes. Known small molecule inhibitors targeting C4 photosynthesis were used to validate the approach. To this end, we tested pyruvate phosphat dikinase (PPDK) inhibitor bisindolymaleimide IV (BIM4) and phosphoenolpyruvat carboxylase (PEPC) inhibitor okanin. Both inhibitors show inhibition of plant photosynthesis at half-maximal inhibitory concentrations (IC50) in the sub-mM range and confirm their potential to act as a new class of C4 selective inhibitors